Pengaruh Kualitas Pelayanan, dan Penetapan Harga Terhadap Keputusan Pembelian Sepeda Motor Vario 150 Pada PT. Gratia Plena Mas Motor Cabang Lahat - Markus, Markus (MOTIVASI, 2019)
ABSTRACT Purpose - This study aims to determine the effect of Service Quality on Purchasing Decisions of Honda Vario 150 Motorcycles at PT. Gratia Plena Mas Lahat Branch, the effect of Pricing on the Purchase Decision of Honda Vario 150 Motorcycles at PT. Gratia Plena Mas Lahat Branch, and Service Quality and Pricing on the Purchase Decision  of Honda Vario 150 Motorcycle at PT. Gratia Plena Mas Lahat Branch.Design/methodology - The sample in this study amounted to 50 respondents who were distributed to consumers specifically motorcycle products with the brand "Honda Vario 150" in Pasar Bawah Village. Data analysis method used is quantitative analysis using validity, reliability, normality, multiple linear regression analysis and average difference test. Findings - Service Quality Results have a positive and significant effect on the decision to purchase a Honda Vario 150 motorcycle at PT. Gratia Plena Mas Lahat Branch. This can be seen from the value of t count> t table (11,227> 2,012). Pricing has a positive and significant influence on the decision to purchase a Honda Vario 150 motorcycle at PT. Gratia Plena Mas Lahat Branch. This can be seen from the value of t count> t table (4,500> 2,012). And Service Quality and Pricing simultaneously have a positive and significant effect on the decision to purchase a Honda Vario 150 at PT. Gratia Plena Mas Lahat Branch. This can be seen from the calculated F value> F table (82.427> 2.25) and the significance value <significance level (?) 0.05 (0.000 <0.05).